2015
DOI: 10.1242/jeb.112862
|View full text |Cite
|
Sign up to set email alerts
|

Divergent physiological responses in laboratory rats and mice raised at high altitude

Abstract: Ecological studies show that mice can be found at high altitude (HAup to 4000 m) while rats are absent at these altitudes, and there are no data to explain this discrepancy. We used adult laboratory rats and mice that have been raised for more than 30 generations in La Paz, Bolivia (3600 m), and compared their hematocrit levels, right ventricular hypertrophy (index of pulmonary hypertension) and alveolar surface area in the lungs. We also used whole-body plethysmography, indirect calorimetry and pulse oxymetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 41 publications
5
26
1
2
Order By: Relevance
“…Overall, these results seem to indicate that responses to hypoxia are more efficient in FVB mice than in SD rats. This is line with our previous findings obtained in the HA colonies of FVB mice and SD rats (Jochmans-Lemoine et al, 2015), in which we concluded that the specific physiological traits observed in laboratory mice at HA could explain why mice are commonly found at HA. By contrast, and as also presented in the Introduction, it is less common to find rats at HA.…”
Section: Hif-1α Expression Is Correlated With Respiratory and Metabolsupporting
confidence: 93%
See 4 more Smart Citations
“…Overall, these results seem to indicate that responses to hypoxia are more efficient in FVB mice than in SD rats. This is line with our previous findings obtained in the HA colonies of FVB mice and SD rats (Jochmans-Lemoine et al, 2015), in which we concluded that the specific physiological traits observed in laboratory mice at HA could explain why mice are commonly found at HA. By contrast, and as also presented in the Introduction, it is less common to find rats at HA.…”
Section: Hif-1α Expression Is Correlated With Respiratory and Metabolsupporting
confidence: 93%
“…We previously compared the physiological adjustments to HA in laboratory Sprague Dawley (SD) rats and FVB mice that have been bred and raised at 3600 m above SL (La Paz, Bolivia) for more than 20 years and over 30 generations. Compared with rats, mice had lower hematocrit and hemoglobin levels, reduced right ventricular hypertrophy (a sign of reduced pulmonary hypertension), increased alveolar surface area and lung volume, higher tidal volume and metabolic rate (Jochmans-Lemoine et al, 2015). Along with the data obtained at HA, we also reported values obtained at SL under normoxic conditions showing that rats and mice had similar lung volume, total alveolar surface area and metabolic rate (JochmansLemoine et al, 2015).…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations